Uji Aktivitas Antioksidan Lotion Ekstrak Etanol Daun Nilam (Pogostemon Cablin Benth) Dengan Metode DPPH (2,2-Diphenyl-1-Picrylhydrazil) - Mawar Rahma Putri; Nerly Juli Pranita Simanjuntak; Novitaria Br Sembiring (Journal of Pharmaceutical and Sciences, 2026)
Introduction: The skin, as the outermost organ of the human body, is continuously exposed to environmental factors, particularly sunlight and free radicals, which can induce oxidative stress leading to skin tissue damage and premature aging. Consequently, topical antioxidants are essential for skin protection. Patchouli leaves (Pogostemon cablin Benth.) are known to contain flavonoid compounds with potential antioxidant properties. Objective: This study aims to evaluate the antioxidant activity of patchouli leaf ethanol extract in lotion formulations using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Methods: This experimental research involved plant determination, extraction of patchouli leaves using the maceration method with 96% ethanol, phytochemical screening, formulation of lotion preparations with varying extract concentrations (1%, 2%, and 3%), physicochemical evaluation of the lotion formulations (including organoleptic properties, pH, homogeneity, viscosity, and spreadability), and antioxidant activity assessment using the DPPH radical scavenging assay. The antioxidant activity was expressed as IC₅₀ values, calculated through linear regression analysis. Results: Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, tannins, and triterpenoids/steroids in the ethanol extract. All lotion formulations demonstrated good physical stability and met the required quality standards for topical preparations, with pH values within the skin-friendly range (4.5-6.5), homogeneous texture, appropriate viscosity (2,000-50,000 cps), and adequate spreadability (5-7 cm). The ethanol extract of patchouli leaves exhibited very strong antioxidant activity with an IC₅₀ value of 0.011 µg/mL, while the formulated lotion maintained considerable antioxidant potential with an IC₅₀ value of 19.11 µg/mL. Conclusion: The ethanol extract of patchouli leaves possesses significant antioxidant activity and can be successfully formulated into a stable lotion preparation that retains its radical-scavenging properties. These findings suggest that patchouli leaf extract holds promising potential for development as a natural antioxidant active ingredient in topical cosmetic products, offering a viable alternative to synthetic antioxidants for skin protection against oxidative stress.